High-film-thickness conductive silver paste and preparation and application thereof

By optimizing the composition and process in the conductive silver paste, a high-film-thick conductive silver paste was prepared, which solved the problem of taking into account the fast drying of low temperature and high performance in the prior art, and achieved high-performance and low-cost conductive silver paste.

CN119889765APending Publication Date: 2025-04-25SHANGHAI BAOYIN ELECTRONICS MATERIALS CO LTD

Patent Information

Application Number
CN202411980837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing conductive silver paste is difficult to balance the requirements of low-temperature fast-drying production and high performance, and the low silver content leads to poor resistance and stability performance.

Method used

The high-thick conductive silver paste is prepared by using a composition of 25% to 30%, an organic binder 6% to 10%, a solvent 60% to 70% and an auxiliary agent 0.5 to 4%, and a high-thick conductive silver paste is prepared by specific process steps such as low-speed dispersion, high-speed dispersion and vacuum filtration.

Benefits of technology

The suitable silk-print viscosity and dense silver powder layout of conductive silver paste are achieved, the line dry film thickness is improved to 3~4μm, the electrochemical and mechanical properties are improved, and the needs of low cost and high performance are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221517880000121
    Figure BDA0005221517880000121
Patent Text Reader

Abstract

The invention relates to the technical field of conductive silver paste, in particular to high-film-thickness conductive silver paste and preparation and application thereof. The high-film-thickness conductive silver paste provided by the invention is characterized by comprising the following components in percentage by mass: 25%-30% of conductive silver powder, 6%-10% of an organic binder, 60%-70% of a solvent and 0.5%-4% of an auxiliary agent, the auxiliary agent is selected from a curing agent, a flatting agent, a thixotropic agent and an adhesion promoter; wherein the sum of the mass percentages of all the components is 100%. Compared with the existing conductive silver paste, the high-film-thickness conductive silver paste provided by the invention has the advantages of high film thickness, fine circuit, compact silver powder arrangement, simple preparation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive silver paste, and in particular to a high-thickness conductive silver paste and the preparation and application thereof. Background Art

[0002] Conductive silver paste, as a key conductive functional material for the preparation of a variety of advanced electronic components and devices, has received extensive attention and research. Currently, low-temperature curing conductive silver paste has been widely used in membrane switch boards, membrane switch keyboards, wireless radio frequency tags, and printed circuits.

[0003] With the development of electronic science and technology in recent years, the electronic devices people need have shown a trend of being thin, light, multifunctional, intelligent and low-cost. This has prompted people to research and develop more advanced and low-cost manufacturing technologies for electronic components, electronic circuit boards and printed circuit boards. From the perspective of competition, the current market has shown a trend of diversification and internationalization. Not only have many domestic and foreign companies joined, but they have also improved their market competitiveness through continuous technological innovation and cost reduction.

[0004] Membrane switches are widely used in computers, aerospace, communications, industrial equipment and office equipment due to their simple structure, beautiful and flat appearance, thin finished products, light touch connection and long service life. Conductive silver paste for membrane switches has lower performance requirements, and the domestic market has increasingly stringent control over its cost. Therefore, seeking conductive silver paste with lower silver content and more stable performance has become a consensus in the industry.

[0005] Patent CN110444316A discloses a low-temperature curing conductive silver paste with high conductivity and low silver content and its preparation method. The raw materials are composed of the following components and weight percentages: 5-30wt% homemade nano-flaky silver powder, 9.6wt% polymer resin, 0.5-3wt% conductive promoter and 57.4-84.9wt% solvent. However, the resin used in the patent is thermosetting 71 resin, and the baking temperature is 140℃ for 45-60min. Its baking time can no longer meet the existing low-temperature quick-drying production requirements; at the same time, the silver content of its embodiment is between 7.5% and 12%, which is too low, and the resistance and stability performance are disadvantageous.

[0006] Patent CN115798782A discloses a multifunctional low-silver conductive silver paste for membrane switches and its preparation method. The raw materials use the following components and weight percentages: 25% to 35% silver powder, 60% to 70% organic carrier, 2% to 5% functional additives, and 2% to 8% organic solvents; the functional additives include polymer interface agents, acetylene carbon black, fumed silica, and wetting agents. The loose density of the silver powder used in the patent conductive silver paste is 0.6 to 1.0 g / cm 3, tap density is 1.0~2.0g / cm 3 In the case of lower silver powder content, the arrangement of silver powder in the circuit is not dense enough, and there is light transmission phenomenon; at the same time, acetylene carbon black is introduced as an auxiliary conductive phase, but its dispersion is poor, which will affect the dielectric constant between the silver powders. Summary of the invention

[0007] In order to solve the above problems, the purpose of the present invention is to provide a high-thickness conductive silver paste and its preparation and application. The conductive silver paste prepared by the present invention has suitable screen printing viscosity and excellent thixotropic recovery ability; the conductive silver paste prepared by the present invention is screen printed, and there is no blocking or self-leakage during the screen printing process, and the screen printing circuit diagram is clear, without any breakpoints and flash; the baking process of the conductive silver paste prepared by the present invention is 140℃ for 1 to 3 minutes, and the silver powder of the screen printing circuit after curing is densely arranged, with excellent light-shielding properties, and the dry thickness can reach 3 to 4μm.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] The first object of the present invention is to provide a high film thickness conductive silver paste, comprising the following components in percentage by mass:

[0010] Conductive silver powder 25% to 30%, organic binder 6% to 10%, solvent 60% to 70%, additive 0.5 to 4%;

[0011] The auxiliary agent is selected from the group consisting of a curing agent, a leveling agent, a thixotropic agent and an adhesion promoter;

[0012] The sum of the mass percentages of the various components is 100%.

[0013] In one embodiment of the present invention, the conductive silver powder is a flaky silver powder with a particle size D10 < 2 μm, a particle size D50 < 5 μm, and a bulk density of 0.35 to 0.4 g / cm 3 , tap density 1.08~1.15g / cm 3 .

[0014] In one embodiment of the present invention, the organic binder is chloroacetic acid resin.

[0015] Preferably, the average molecular weight of the chlorovinyl resin is 48,000, the K value is 59, and it is Dow VAGH-003A.

[0016] In one embodiment of the present invention, the solvent is selected from one or more of DBE (dibasic acid ester), isophorone, PMA (propylene glycol methyl ether acetate), PM (propylene glycol methyl ether), and ethyl acetate.

[0017] In one embodiment of the present invention, the solvent is a mixture of DBE (high boiling range solvent), isophorone (high boiling range solvent), PMA (medium boiling range solvent), PM (medium boiling range solvent) and ethyl acetate (low boiling range solvent).

[0018] In one embodiment of the present invention, the mixed solvent is baked at a low temperature of 140°C, and its components contain ethyl acetate with a lower boiling point, which can evaporate quickly in a short time, so that the edge diffusion speed of the conductive ink is slowed down, and the resolution of the ink is effectively improved; the high-boiling range DBE and isophorone solvents can take into account the network storage time during ink printing, so as not to cause the phenomenon of dry network in a short time; the medium-boiling range PM and PMA solvents have a boiling point of 120-150°C, and their volatilization speed is moderate. After the low-boiling point solvent evaporates in the coating, it is beneficial to the leveling of the coating to form a dense paint film; at the same time, it can form a smooth volatilization gradient with high and low boiling range solvents, reduce internal stress during baking, and make the distribution of additives and silver powder more uniform.

[0019] In one embodiment of the present invention, the curing agent is a blocked isocyanate curing agent; the isocyanate group NCO content is 6.5-12.5%, and the deblocking temperature is 90-130° C., including one or more of MF-B60X, MF-K60X, XB-G282, TPA-B80X, 17B-60PX, SBN-70D, SH-110, and SH-120;

[0020] The leveling agent is selected from one or more of silicone leveling agent BYK-333, polyvinyl butyral or polyacrylate; preferably, the leveling agent is BYK-333 leveling agent, because it has the characteristics of drastically reducing surface tension, wetting the surface of harsh substrates, excellent anti-cratering, increasing surface smoothness and gloss, and improving anti-adhesion, thereby reducing the probability of short lines when fine lines are printed;

[0021] The thixotropic agent is selected from one or more of fumed silica, hydrogenated castor oil, polyamide wax, organic bentonite or hydroxyethyl cellulose; preferably, the thixotropic agent is organic bentonite, which has good thickening, thixotropy, suspension stability, high temperature stability, lubricity, film-forming property, water resistance and chemical stability, fast recovery speed, short time, and good anti-sag performance;

[0022] The adhesion promoter is selected from one or more of polyesters, epoxy phosphate polymers, polypropylene polymers, and silane coupling agents; preferably, the adhesion promoter is a polyester adhesion promoter, which has good compatibility with the conductive silver paste. In addition to enhancing the adhesion of the conductive silver paste, it can also improve the water resistance, salt spray resistance, flexibility and impact resistance of the conductive silver paste.

[0023] A second object of the present invention is to provide a method for preparing a high-thickness conductive silver paste, comprising the following steps:

[0024] (S1) adding an organic binder to a solvent in batches and heating and mixing, and filtering to obtain a carrier;

[0025] (S2) mixing the thixotropic agent and the solvent, and filtering to obtain a thixotropic agent solution;

[0026] (S3) sequentially adding the thixotropic agent solution, curing agent, leveling agent, adhesion promoter, solvent, and conductive silver powder prepared in step (S2) to the carrier prepared in step (S1), and then performing a low-speed dispersion treatment to obtain a mixed slurry;

[0027] (S4) alternately grinding and high-speed dispersing the mixed slurry prepared in step (S3) to obtain a conductive silver paste;

[0028] (S5) The conductive silver paste prepared in step (S4) is subjected to vacuum filtration treatment (to separate large particle impurities generated during the grinding process), and then subjected to homogenous stirring treatment (to degas the silver paste and prevent the silver powder from settling) to obtain a high film thickness conductive silver paste.

[0029] In one embodiment of the present invention, in step (S1), during the heating process, the temperature is 50 to 90° C.; during the filtration process, the mesh size of the sieve is 250 to 300 mesh;

[0030] In step (S2), during the filtration process, the mesh size of the sieve is 250-300 mesh;

[0031] In step (S5), during the filtering process, the mesh size of the sieve is 250-300 meshes.

[0032] In one embodiment of the present invention, in step (S3), during the low-speed dispersion treatment, the low-speed dispersion rate is 800 to 1200 rpm / min, and the time is 2.5 to 3.5 min;

[0033] In step (S4), during the high-speed dispersion treatment, the high-speed dispersion rate is 1800-2200 r / min, and the time is 4-6 min; the fineness of the conductive silver paste is less than 5 μm, and the viscosity is 10 Pa·S-12 Pa·S.

[0034] The high-thickness conductive silver paste provided by the invention has the advantages of high film thickness, fine circuits, dense arrangement of silver powder, simple preparation, and the like.

[0035] The third object of the present invention is to provide an application of a high-thickness conductive silver paste in the preparation of a membrane switch.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The conductive silver powder used in the high-thickness conductive silver paste of the present invention has lower bulk density and tap density, and has sufficient circuit screen printing filling at a silver powder content of 27% to 30%. The prepared conductive silver paste has suitable screen printing viscosity and dense silver powder overlap arrangement, and the dry film thickness of the conductive silver paste circuit is increased from the original 1 to 2 μm to 3 to 3.5 μm;

[0038] (2) The chloroacetic acid resin selected for the high-thickness conductive silver paste of the present invention is a ternary hydroxychloroacetic acid quick-drying resin, which, as a conductive film matrix skeleton, has the characteristics of good quick-drying ability, high bonding strength, and good silver powder dispersion and arrangement performance. Under the premise of meeting the mechanical properties, the electrochemical properties are also excellent;

[0039] (3) The solvents selected for the high-thickness conductive silver paste of the present invention include high-boiling range, medium-boiling range and low-boiling range solvents, which can evaporate in layers smoothly during the baking process. The solubility, surface tension and viscosity of the conductive paste are controlled as the solvent evaporates, and the internal arrangement of the flaky conductive silver powder and the distribution of the additives will not deteriorate, thereby ensuring the smooth appearance of the coating, the compact structure and the stability of the performance; at the same time, the solvent contains both polar groups and non-polar groups, so that it has good wetting and coating capabilities for both organic components and non-polar components;

[0040] (4) The high-thickness conductive silver paste of the present invention uses organic bentonite as a thixotropic agent, which has good thickening, thixotropy, suspension stability, high-temperature stability, lubricity, film-forming, water resistance and chemical stability. Its introduction improves the thixotropy of the conductive silver paste, ensures that the conductive silver paste has good fluidity under high shear force, and can maintain the shape of the grid line under low shear force, which is conducive to improving the grid line film thickness and line refinement. The dry film thickness of the conductive silver paste line is increased from the original 3-3.5μm to a stable 4μm, which has reached the film thickness of the conductive silver paste with a silver powder content of 40%-50% after drying, and its conductive line width is close to the film line width, the line is straight, and the brightness is consistent; at the same time, it improves the instability of the conductive paste storage and high-speed dispersion and stirring process, and improves the problems of burning wire and large resistance caused by the low film thickness of the conductive silver paste. The performance of the organic bentonite itself is also very helpful to the weather resistance and high-temperature stability of the conductive silver paste.

[0041] (5) The curing agent used in the high-thickness conductive silver paste of the present invention has a low deblocking temperature of 130°C, and has excellent compatibility and weather resistance in the paste. Its introduction improves the cross-linking degree of the resin and improves the resistance and adhesion properties of the conductive paste. The selected leveling agent BYK-333 can drastically reduce the surface tension of the coating and printing ink, improve the wetting effect of the substrate, prevent shrinkage holes, and increase the surface smoothness and gloss. Its introduction improves the bubble and shrinkage hole problems caused by high resin content, and improves the dotted line and pinhole problems in the screen printing process of low-silver conductive silver paste; the selected polyester adhesion promoter has good compatibility with the conductive silver paste. In addition to enhancing the adhesion of the conductive silver paste, it can also improve the water resistance, salt spray resistance, flexibility and impact resistance of the conductive silver paste. DETAILED DESCRIPTION

[0042] The present invention is described in detail below with reference to specific embodiments.

[0043] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.

[0044] The percentages mentioned below are all the proportions in high film thickness conductive silver paste.

[0045] Example 1

[0046] This embodiment provides a high-thickness conductive silver paste, comprising the following components in percentage by mass:

[0047] Conductive silver powder 25%; organic binder 9%; curing agent 0.5%; leveling agent 0.5%; thixotropic agent 0.8%; solvent 64.2%;

[0048] The conductive silver powder is a flaky silver powder, the particle size D10 of the conductive silver powder is less than 2 μm, the particle size D50 is less than 5 μm, and the bulk density is 0.35 to 0.4 g / cm 3 , tap density is 1.08~1.15g / cm 3 ;

[0049] The organic binder is chlorovinyl resin, with an average molecular weight of 48,000, a K value of 59, and Dow VAGH-003A;

[0050] The organic solvent is a mixture of DBE, isophorone, PMA, PM and ethyl acetate;

[0051] The curing agent is a blocked isocyanate curing agent TPA-B80X, with an isocyanate group NCO content of 12.5%, a solid content of 80%, and a deblocking temperature of 130°C;

[0052] The leveling agent is an organic silicon leveling agent BYK-333;

[0053] The thixotropic agent is organic bentonite, model BP-186;

[0054] The high-thickness conductive silver paste of this embodiment is prepared by the following method:

[0055] (S1) Preparation of chloroacetic acid resin carrier: DBE and isophorone are added to a reactor, and the temperature is gradually raised to 80° C., and then 1 / 3 of the total mass of the chloroacetic acid resin is stirred and added to the reactor from the mouth of the reactor. The remaining mass of the chloroacetic acid resin is added for 1 hour, and 1 / 3 of the total mass of the chloroacetic acid resin is added every 0.5 hour. After the addition is completed, stirring and dissolving are continued for 2 hours; then, the reactor is cooled to 50° C., PM, PMA, and ethyl acetate are added to the reactor, reacted for 1 hour, and the chloroacetic acid resin carrier (viscosity is 10 Pa.s (NDJ-79 rotational viscometer, II unit, 75 rpm, 25° C.)) is obtained by circulating and filtering, and stored in the dark;

[0056] Wherein, the weight percentage of each component is as follows:

[0057] Chlorovinyl resin: 9%;

[0058] DBE: 10.8%;

[0059] Isophorone: 5.4%;

[0060] PM: 3.6%;

[0061] PMA: 1.8%;

[0062] Ethyl acetate: 1.8%;

[0063] (S2) Activation of thixotropic agent: PMA and DBE solvents were added to a stirred tank, and organic bentonite was added with stirring at a speed of 1500 rpm for 1 hour. The thixotropic agent solution was obtained after filtering through a 300-mesh sieve and sealed for storage;

[0064] Wherein, the weight percentage of each component is as follows:

[0065] Organic bentonite: 0.8%;

[0066] PMA: 1.6%;

[0067] DBE: 1.6%;

[0068] (S3) Preparation of mixed slurry: The activated thixotropic agent solution of step (S2), TPA-B80X curing agent (0.5%), BYK-333 leveling agent (0.5%) are added to the chlorovinyl resin carrier obtained in step (S1) in sequence, and finally DBE (37.6%) and conductive silver powder (25%) are added. The obtained mixture is placed in a disperser for low-speed dispersion (the low-speed dispersion rate is 1000 rpm / min, and the time is 3 min) to ensure that the mixture is completely wetted and the slurry is silver-gray, thereby obtaining a mixed slurry;

[0069] The batching process uses a Mettler BBA211 electronic scale as a weighing tool, and with the recording component, the operator can add raw materials with corresponding codes according to the panel display value, with an accuracy of one ten-thousandth;

[0070] (S4) Preparation of conductive silver paste: The mixed slurry obtained in step (S3) is dispersed and ground in a three-roll mill (grinding treatment and high-speed dispersion treatment are performed alternately. During the grinding process, the roller spacing of the three-roll mill is gradually reduced, and sheeting is not allowed to occur. After each dispersion in the three-roll mill, it must be dispersed in a high-speed disperser; during the high-speed dispersion treatment, the high-speed dispersion rate is 2000 rpm / min, and the time is 5 min), and the fineness and viscosity of the slurry after grinding and dispersion are controlled.

[0071] The fineness is controlled by a scraper fineness meter, and the final fineness is controlled below 5μm. The slurry that does not meet the fineness requirement is repeatedly dispersed and ground until the fineness requirement is met.

[0072] The viscosity is controlled by NDJ-79 rotational viscometer, and the slurry that does not meet the viscosity range is adjusted by diluent and thixotropic agent.

[0073] Conduct quality inspection on the conductive silver paste that meets the fineness and viscosity requirements to ensure that it meets the production quality requirements. The quality inspection includes resistance, hardness, adhesion, line quality and other properties;

[0074] The screen used for quality inspection is a stainless steel screen with a mesh size of 300.

[0075] (S5) vacuum filtration: vacuum filtration of the conductive silver paste prepared in step (S4) to separate large particle impurities generated during the grinding process;

[0076] (S6) Homogenizing and stirring: After step (S5), a homogenizer is used to degas the silver paste and prevent the silver powder from settling, thereby obtaining a high-thickness conductive silver paste.

[0077] Example 2

[0078] This embodiment provides a high-thickness conductive silver paste, comprising the following components in percentage by mass:

[0079] Conductive silver powder 27.5%; organic binder 7.8%; curing agent 0.5%; leveling agent 0.3%; thixotropic agent 0.5%; adhesion promoter 0.3%; solvent 63.1%;

[0080] The conductive silver powder is a flaky silver powder, the particle size D10 of the conductive silver powder is less than 2 μm, the particle size D50 is less than 5 μm, and the bulk density is 0.35 to 0.4 g / cm 3 , tap density is 1.08~1.15g / cm 3 ;

[0081] The organic binder is chlorovinyl resin, with an average molecular weight of 48,000, a K value of 59, and Dow VAGH-003A;

[0082] The organic solvent is a mixture of DBE, isophorone, PMA, PM and ethyl acetate;

[0083] The curing agent is a blocked isocyanate curing agent TPA-B80X, with an isocyanate group NCO content of 12.5%, a solid content of 80%, and a deblocking temperature of 130°C;

[0084] The leveling agent is an organic silicon leveling agent BYK-333;

[0085] The thixotropic agent is organic bentonite, model BP-186;

[0086] The adhesion promoter is polyester, model LD-3167, and is intended to improve the silver loss and interlayer adhesion problems caused by the weight reduction of the organic binder.

[0087] The high-thickness conductive silver paste of this embodiment is prepared by the following method:

[0088] (S1) Preparation of chloroacetic acid resin carrier: DBE and isophorone are added to a reactor, and the temperature is gradually raised to 80° C., and then 1 / 3 of the total mass of the chloroacetic acid resin is stirred and added to the reactor from the mouth of the reactor. The remaining mass of the chloroacetic acid resin is added for 1 hour, and 1 / 3 of the total mass of the chloroacetic acid resin is added every 0.5 hour. After the addition is completed, stirring and dissolving are continued for 2 hours; then, the reactor is cooled to 50° C., PM, PMA, and ethyl acetate are added to the reactor, reacted for 1 hour, and the chloroacetic acid resin carrier (viscosity is 10 Pa.s (NDJ-79 rotational viscometer, II unit, 75 rpm, 25° C.)) is obtained by circulating and filtering, and stored in the dark;

[0089] Wherein, the weight percentage of each component is as follows:

[0090] Chlorovinyl resin: 7.8%;

[0091] DBE: 10.9%;

[0092] Isophorone: 5.4%;

[0093] PM: 3.2%;

[0094] PMA: 3.2%;

[0095] Ethyl acetate: 0.32%;

[0096] (S2) Activation of thixotropic agent: PMA and DBE solvents were added to a stirred tank, and organic bentonite was added with stirring at a speed of 1500 rpm for 1 hour. The thixotropic agent solution was obtained after filtering through a 300-mesh sieve and sealed for storage;

[0097] Wherein, the weight percentage of each component is as follows:

[0098] Organic bentonite: 0.5%;

[0099] PMA: 1%;

[0100] DBE: 1%;

[0101] (S3) Preparation of mixed slurry: adding the activated thixotropic agent solution of step (S2), TPA-B80X curing agent (0.5%), BYK-333 leveling agent (0.3%) and polyester adhesion promoter (0.3%) to the chlorovinyl resin carrier obtained in step (S1) in sequence, and finally adding 38.08% by mass of DBE and 27.5% of conductive silver powder, and placing the obtained mixture in a disperser for low-speed dispersion (low-speed dispersion rate of 1000 rpm / min, time of 3 min) to ensure that the mixture is completely wetted and the slurry is silver-gray, thereby obtaining a mixed slurry;

[0102] The batching process uses a Mettler BBA211 electronic scale as a weighing tool, and with the recording component, the operator can add raw materials with corresponding codes according to the panel display value, with an accuracy of one ten-thousandth;

[0103] (S4) Preparation of conductive silver paste: The mixed slurry obtained in step (S3) is dispersed and ground in a three-roll mill (grinding treatment and high-speed dispersion treatment are performed alternately. During the grinding process, the roller spacing of the three-roll mill is gradually reduced, and sheeting is not allowed to occur. After each dispersion in the three-roll mill, it must be dispersed in a high-speed disperser; during the high-speed dispersion treatment, the high-speed dispersion rate is 2000 rpm / min, and the time is 5 min), and the fineness and viscosity of the slurry after grinding and dispersion are controlled.

[0104] The fineness is controlled by a scraper fineness meter, and the final fineness is controlled below 5μm. The slurry that does not meet the fineness requirement is repeatedly dispersed and ground until the fineness requirement is met.

[0105] The viscosity is controlled by NDJ-79 rotational viscometer, and the slurry that does not meet the viscosity range is adjusted by diluent and thixotropic agent.

[0106] Conduct quality inspection on the conductive silver paste that meets the fineness and viscosity requirements to ensure that it meets the production quality requirements. The quality inspection includes resistance, hardness, adhesion, line quality and other properties;

[0107] The screen used for quality inspection is a stainless steel screen with a mesh size of 300.

[0108] (S5) vacuum filtration: vacuum filtration of the conductive silver paste prepared in step (S4) to separate large particle impurities generated during the grinding process;

[0109] (S6) Homogenizing and stirring: After step (S5), a homogenizer is used to degas the silver paste and prevent the silver powder from settling, thereby obtaining a high-thickness conductive silver paste.

[0110] Example 3

[0111] This embodiment provides a high-thickness conductive silver paste, comprising the following components in percentage by mass:

[0112] Conductive silver powder 30%; organic binder 6%; curing agent 0.35%; leveling agent 0.3%; thixotropic agent 0.3%; adhesion promoter 0.5%; solvent 62.55%;

[0113] The conductive silver powder is a flaky silver powder, the particle size D10 of the conductive silver powder is less than 2 μm, the particle size D50 is less than 5 μm, and the bulk density is 0.35 to 0.4 g / cm 3 , tap density is 1.08~1.15g / cm 3 ;

[0114] The organic binder is chlorovinyl resin, with an average molecular weight of 48,000, a K value of 59, and Dow VAGH-003A;

[0115] The organic solvent is a mixture of DBE, isophorone, PMA, PM and ethyl acetate;

[0116] The curing agent is a blocked isocyanate curing agent TPA-B80X, with an isocyanate group NCO content of 12.5%, a solid content of 80%, and a deblocking temperature of 130°C;

[0117] The leveling agent is an organic silicon leveling agent BYK-333;

[0118] The thixotropic agent is organic bentonite, model BP-186;

[0119] The adhesion promoter is polyester, model LD-3167, and is intended to improve the silver loss and interlayer adhesion problems caused by the weight reduction of the organic binder.

[0120] The high-thickness conductive silver paste of this embodiment is prepared by the following method:

[0121] (S1) Preparation of chloroacetic acid resin carrier: DBE and isophorone are added to a reactor, and the temperature is gradually raised to 80° C., and then 1 / 3 of the total mass of the chloroacetic acid resin is stirred and added to the reactor from the mouth of the reactor. The remaining mass of the chloroacetic acid resin is added for 1 hour, and 1 / 3 of the total mass of the chloroacetic acid resin is added every 0.5 hour. After the addition is completed, stirring and dissolving are continued for 2 hours; then, the reactor is cooled to 50° C., PM, PMA, and ethyl acetate are added to the reactor, reacted for 1 hour, and the chloroacetic acid resin carrier (viscosity is 10 Pa.s (NDJ-79 rotational viscometer, II unit, 75 rpm, 25° C.)) is obtained by circulating and filtering, and stored in the dark;

[0122] Wherein, the weight percentage of each component is as follows:

[0123] Chlorovinyl resin: 6%;

[0124] DBE: 9%;

[0125] Isophorone: 4.5%;

[0126] PM: 3%;

[0127] PMA: 3%;

[0128] Ethyl acetate: 1.2%;

[0129] (S2) Activation of thixotropic agent: PMA and DBE solvents were added to a stirred tank, and organic bentonite was added with stirring at a speed of 1500 rpm for 1 hour. The thixotropic agent solution was obtained after filtering through a 300-mesh sieve and sealed for storage;

[0130] Wherein, the weight percentage of each component is as follows:

[0131] Organic bentonite: 0.3%;

[0132] PMA: 0.6%;

[0133] DBE: 0.6%;

[0134] (S3) Preparation of mixed slurry: The activated thixotropic agent solution of step (S2), TPA-B80X curing agent (0.35%), BYK-333 leveling agent (0.3%) and polyester adhesion promoter (0.5%) are added to the chlorovinyl resin carrier obtained in step (S1) in sequence, and finally 40.65% by mass of DBE and conductive silver powder (30%) are added, and the obtained mixture is placed in a disperser for low-speed dispersion (the low-speed dispersion rate is 1000 rpm / min, and the time is 3 min) to ensure that the mixture is completely wetted and the slurry is silver-gray, thereby obtaining a mixed slurry;

[0135] The batching process uses a Mettler BBA211 electronic scale as a weighing tool, and with the recording component, the operator can add raw materials with corresponding codes according to the panel display value, with an accuracy of one ten-thousandth;

[0136] (S4) Preparation of conductive silver paste: The mixed slurry obtained in step (S3) is dispersed and ground in a three-roll mill (grinding treatment and high-speed dispersion treatment are performed alternately. During the grinding process, the roller spacing of the three-roll mill is gradually reduced, and sheeting is not allowed to occur. After each dispersion in the three-roll mill, it must be dispersed in a high-speed disperser; during the high-speed dispersion treatment, the high-speed dispersion rate is 2000 rpm / min, and the time is 5 min), and the fineness and viscosity of the slurry after grinding and dispersion are controlled.

[0137] The fineness is controlled by a scraper fineness meter, and the final fineness is controlled below 5μm. The slurry that does not meet the fineness requirement is repeatedly dispersed and ground until the fineness requirement is met.

[0138] The viscosity is controlled by NDJ-79 rotational viscometer, and the slurry that does not meet the viscosity range is adjusted by diluent and thixotropic agent.

[0139] Conduct quality inspection on the conductive silver paste that meets the fineness and viscosity requirements to ensure that it meets the production quality requirements. The quality inspection includes resistance, hardness, adhesion, line quality and other properties;

[0140] The screen used for quality inspection is a stainless steel screen with a mesh size of 300.

[0141] (S5) vacuum filtration: vacuum filtration of the conductive silver paste prepared in step (S4) to separate large particle impurities generated during the grinding process;

[0142] (S6) Homogenizing and stirring: After step (S5), a homogenizer is used to degas the silver paste and prevent the silver powder from settling, thereby obtaining a high-thickness conductive silver paste.

[0143] Comparative Example 1

[0144] This comparative example 1 is compared with embodiment 3, except for the following conditions, all other conditions are the same.

[0145] Conductive silver powder is a high tap density conductive silver powder (the D50 particle size of the conductive silver powder is 0.5-1.0 μm, and the tap density is 3.0-4.5 g / cm 3 ; Bulk density is 1.5~2.0g / cm 3 ).

[0146] Comparative Example 2

[0147] This comparative example 1 is compared with embodiment 3, except for the following conditions, all other conditions are the same.

[0148] The solvent was changed to a mixture of PMA, PM, and ethyl acetate;

[0149] In Example 3, DBE was replaced by PMA, and isophorone was replaced by PM.

[0150] Comparative Example 3

[0151] This comparative example 1 is compared with embodiment 3, except for the following conditions, all other conditions are the same.

[0152] The solvent was a mixture of DBE, isophorone, and ethyl acetate;

[0153] In Example 3, PMA was replaced by DBE, and PM was replaced by isophorone.

[0154] Comparative Example 4

[0155] This comparative example 1 is compared with embodiment 3, except for the following conditions, all others are the same.

[0156] The solvent was a mixture of DBE, isophorone, PMA, and PM;

[0157] The ethyl acetate in Example 3 was replaced with DBE.

[0158] The performance of the high-thickness conductive silver paste prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested. The test results are listed in Table 1:

[0159] Table 1: High film thickness conductive silver paste performance test results

[0160]

[0161] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high film thickness conductive silver paste, characterized in that: The following components are included in mass percentage: Conductive silver powder 25% to 30%, organic binder 6% to 10%, solvent 60% to 70%, additive 0.5 to 4%; The auxiliary agents include curing agent, leveling agent, thixotropic agent and adhesion promoter; The sum of the mass percentages of the various components is 100%.

2. The high film thickness conductive silver paste according to claim 1, characterized in that: The conductive silver powder is a flaky silver powder, with a particle size D10 < 2 μm, a particle size D50 < 5 μm, and a bulk density of 0.35-0.4 g / cm 3 , tap density 1.08~1.15g / cm 3 .

3. The high film thickness conductive silver paste according to claim 1, characterized in that: The organic binder is chloroacetic acid resin.

4. The high film thickness conductive silver paste according to claim 1, characterized in that: The solvent is selected from one or more of DBE, isophorone, PMA, PM, and ethyl acetate.

5. The high film thickness conductive silver paste according to claim 4, characterized in that: The solvent is a mixture of DBE, isophorone, PMA, PM and ethyl acetate.

6. The high film thickness conductive silver paste according to claim 1, characterized in that: The curing agent is a blocked isocyanate curing agent; The leveling agent is selected from one or more of organic silicon leveling agent BYK-333, polyvinyl butyral or polyacrylate; The thixotropic agent is selected from one or more of fumed silica, hydrogenated castor oil, polyamide wax, organic bentonite or hydroxyethyl cellulose; The adhesion promoter is selected from one or more of polyesters, epoxy phosphate polymers, polypropylene polymers, and silane coupling agents.

7. A method for preparing a high-thickness conductive silver paste as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: (S1) adding an organic binder to a solvent in batches and heating and mixing, and filtering to obtain a carrier; (S2) mixing the thixotropic agent and the solvent, and filtering to obtain a thixotropic agent solution; (S3) sequentially adding the thixotropic agent solution, curing agent, leveling agent, adhesion promoter, solvent, and conductive silver powder prepared in step (S2) to the carrier prepared in step (S1), and then performing a low-speed dispersion treatment to obtain a mixed slurry; (S4) alternately grinding and high-speed dispersing the mixed slurry prepared in step (S3) to obtain a conductive silver paste; (S5) The conductive silver paste prepared in step (S4) is subjected to vacuum filtration treatment, and then subjected to homogenization stirring treatment to obtain a high-thickness conductive silver paste.

8. The method for preparing a high-thickness conductive silver paste according to claim 7, characterized in that: In step (S1), during the heating process, the temperature is 50-90° C.; during the filtering process, the mesh size of the sieve is 250-300 mesh; In step (S2), during the filtration process, the mesh size of the sieve is 250-300 mesh; In step (S5), during the filtering process, the mesh size of the sieve is 250-300 meshes.

9. The method for preparing a high-thickness conductive silver paste according to claim 7, characterized in that: In step (S3), during the low-speed dispersion treatment, the low-speed dispersion rate is 800 to 1200 rpm / min, and the time is 2.5 to 3.5 min; In step (S4), during the high-speed dispersion treatment, the high-speed dispersion rate is 1800-2200 r / min, and the time is 4-6 min; the fineness of the conductive silver paste is less than 5 μm, and the viscosity is 10 Pa·S-12 Pa·S.

10. Use of the high-thickness conductive silver paste according to any one of claims 1 to 6 in preparing a membrane switch.

Citation Information

Patent Citations

  • Low-temperature curing conductive silver paste with high conductivity and low silver content and preparation method thereof

    CN110444316A

Cited By

  • Conductive silver paste having high film thickness, and preparation and use thereof

    WO2026143964A1